MULTICULTURAL PERSPECTIVE URGENCY IN ISLAMIC RELIGIOUS EDUCATION STUDYING IN GENERAL UNIVERSITY - Yani, Muhammad Turhan (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2018)
The urgency of multicultural perspective in the lectures (studying or instructional) of Islamic Religious Education (PAI) at General University reviews as follows: (1) the latest PAI curriculum at university is directed to the means of developing moderate and tolerant attitude living in the midst of multicultural and plural society, even if the subject portion about that seems less (2) lately there is a phenomenon of religious attitude that tend to be exclusive to some college students, so that the reality of social interaction is less able to live harmoniously with the different background of college students community, especially different religious; (3) the development of religious groups that tend to radical and exclusive among Muslim students at General University.